If it's not what You are looking for type in the equation solver your own equation and let us solve it.
62=2(b+12)
We move all terms to the left:
62-(2(b+12))=0
We calculate terms in parentheses: -(2(b+12)), so:We get rid of parentheses
2(b+12)
We multiply parentheses
2b+24
Back to the equation:
-(2b+24)
-2b-24+62=0
We add all the numbers together, and all the variables
-2b+38=0
We move all terms containing b to the left, all other terms to the right
-2b=-38
b=-38/-2
b=+19
| 6x=3=21 | | 11-2h=1 | | 5425=(15500)(8.75)(t) | | 12-4=c-5 | | 25(4x)=6x^2+4x | | 9(2x-3)=63 | | 2(3+w)=14 | | 8x+26=10 | | 4+d=3+12 | | 5(2h+10)=40 | | 9=c+14/3 | | 1+2x=5(x+2)-4(x-3) | | 2x+(-4)=10 | | 8+H=n | | 12x+22=13x+10 | | c+19=4c-8 | | M=r/Q | | -4x/9=16 | | -2x+4=7(x-3 | | 4(2x-7)=8x-21 | | 9+18v=20v-15 | | r=M/Q | | -6+2v=3+9+5v | | 15-5=13-a | | p=24=7p | | a9+6=11 | | 12x+20=13x+9 | | 4x-18+2x+2=2 | | -4r+2=4-6r | | 12x-19=9(x-2)+3x | | 11x+2=11x-1 | | 10.4+n=21.2 |